Transformasi Kerohanian Siswa di Era Digital: Pendekatan Baru dalam Pendidikan Agama Kristen - Fredik Melkias Boiliu; Sara Yemima Purba; Agustus Laia (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The development of digital technology has changed the educational landscape, including Christian religious education. In the current digital era, students are required to continue to be connected to technology so that it becomes a new approach in Christian religious education. Therefore, this is important to accommodate students' spiritual transformation. This research aims to explore the challenges and opportunities in integrating Christian religious education with digital technology, as well as presenting new approaches that can be used by educators. This research uses descriptive qualitative methods with literature studies. The results of this research will examine new approach methods in learning Christian religious education which include the use of mobile applications, online learning platforms, and the use of multimedia content that is relevant to the context of students' lives. Thus, with this approach, it is hoped that students can be more involved, connected, and inspired in the Christian religious learning experience, resulting in a deeper and more sustainable spiritual transformation in this digital era.